2022
DOI: 10.1523/jneurosci.1494-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Shapes the Quality of Tactile Percepts Evoked through Electrical Stimulation of the Nerves

Abstract: Electrical stimulation of the peripheral nerves of human participants provides a unique opportunity to study the neural determinants of perceptual quality using a causal manipulation. A major challenge in the study of neural coding of touch has been to isolate the role of spike timing -at the scale of milliseconds or tens of milliseconds -in shaping the sensory experience.In the present study, we address this question by systematically varying the frequency (PF) of electrical stimulation pulse trains delivered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…As expected from prior psychometric studies of sensory stimulation ( Graczyk et al, 2016 , 2022 ; Charkhkar et al, 2018 ), the sensation modality and intensity depended strongly on the stimulation levels set by the participant. When the stimulation levels were low, the participant described the stimulation-elicited sensations as “tingly” or “a very light tingling.” When the stimulation levels were high, the participant explained how the sensation modality changed:…”
Section: Resultssupporting
confidence: 69%
“…As expected from prior psychometric studies of sensory stimulation ( Graczyk et al, 2016 , 2022 ; Charkhkar et al, 2018 ), the sensation modality and intensity depended strongly on the stimulation levels set by the participant. When the stimulation levels were low, the participant described the stimulation-elicited sensations as “tingly” or “a very light tingling.” When the stimulation levels were high, the participant explained how the sensation modality changed:…”
Section: Resultssupporting
confidence: 69%
“…Similarly, George et al [17] showed that intensity discrimination was better at lower f s (12.5 -87.5 Hz) than higher frequencies (50 -200 Hz). A recent study into the influence of intraneural stimulation frequency and pulse width found that participants were able to discriminate frequencies in the range of 2 -∼50 Hz, but that ability broke down beyond a stimulus frequency of 60 Hz [41]. One other study including f s up to 500 Hz did find a linear relationship between f s and perception magnitude [9].…”
Section: Discussionmentioning
confidence: 99%
“…None of the electrodes in any of the participant’s arrays elicited an ICMS sensation that was described as resembling vibration in prior characterization experiments, even when testing a variety of stimulation parameters. Only a few recent studies have started to systematically characterize the relationship between stimulation parameters and the perceived quality of artificial touch [25], [39]. When future technology enables us to selectively activate specific neurons in somatosensory cortex, likely creating more natural-feeling percepts, it would be interesting to repeat these tests.…”
Section: Discussionmentioning
confidence: 99%